Song and dance man - Ackerman, Karen, 1951-; Gammell, Stephen (New York : Distributed by Random House, Distributed by Random House, 1988)
Grandpa demonstrates for his visiting grandchildren some of the songs, dances, and jokes he performed when he was a vaudeville entertainer.
Keywords: Entertainers -- Fiction; Grandfathers -- Fiction